Pengaruh Pertumbuhan Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan Pada Sub Sektor Farmasi di BEI - Luhde Widya Karuni (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of company growth and profitability on firm value simultaneously or partially. The research design used is quantitative causal. The subjects of this research are pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange and the objects of research are company growth, profitability and firm value. The data collection technique used was population, where the population used was 7 companies. Data were collected by recording documents and analyzed by multiple linear regression analysis. The results showed that (1) company growth and profitability had a significant effect on firm value of 55,5%, (2) company growth has no effect on firm value(3) profitability had a significant positive effect on firm value. Keywords: Company Growth, Firm Value, Profitability